Leveraging Technology for Seamless Learning Transfer: A Position for Enhanced Educational Outcomes (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The effective transfer of learning whereby acquired knowledge, skills and competencies are applied in real-world situations remains a crucial goal for teachers and instructors. With the fast advancement of digital technologies, new opportunities have emerged to improve and support this process. This paper examines the role of technology in providing seamless learning transfer across educational settings. It explores how tools like learning management system (LMS), mobile learning applications, and data analytics create adaptive, engaging, and relevant learning experiences. These technologies not only improve knowledge retention and engagement but also enables just-in-time learning and performance support in real-world environment. The paper further considers the pedagogical and theoretical frameworks underpinning technology-enhanced learning transfer. Challenges such as digital fatigue, resistance to new digital tools and over reliance on technology were also discussed. It recommended among others that Institutions should ensure that learners are trained in digital skills that will enable them leverage the use of digital tools for learning transfer.